Toilets at last : perceptions of the users of 'porta potty' toilets in Jim Se Bos informal settlement in Phillipi, Cape Town - Stewart, Clint (My University, 2014)
South Africa has one of the most progressive legislative and policy frameworks for water services in the world, which includes a constitutional right to water and a national Free Basic Water policy (COHRE, 2008). However, the stark reality is that although South Africa has these progressive policies, the sanitation challenge still needs to be overcome. The growing sanitation backlog and the eradication of the bucket system has become a difficult and emotive topic. Many South Africans live in extreme poverty and in informal settlements which do not have adequate sanitation available. Generally, within these informal settlements, households are forced to share toilet facilities, and to walk far distances as the toilets are poorly located, badly maintained and users of these toilets are exposed to danger and violent crimes. This study explores perceptions of the users of ‘porta potty’ toilets in Jim Se Bos informal settlement in Phillipi, Cape Town. Understanding the users’ socio‐cultural perceptions of the porta potty toilet will contribute to future policy making, as the information can be used to improve the future roll‐out of the technology in order to make it more acceptable. The study was qualitative in nature and used a phenomenological research design. A total of 20 community members were invited of which nine respondents comprising of eight residents of Jim Se Bos informal settlement and one employee of the municipality participated in the study. The sample was selected by a convenience sampling method. Semi‐structured interviews were conducted to collect data for the study. The data were analysed by means of content analysis, which enabled the researcher to identify important themes for the study. The findings of the study revealed that perceptions of the users of ‘porta potty’ toilets were positive and that everyone accepted the sanitation system. The participants recommended that the municipality should roll out the porta potty sanitation system in other informal settlements. This recommendation is a vote of confidence for the system and that it is seen to provide the necessary relief from unsafe and vandalised sanitation systems. In conclusion, the porta potty was accepted as being a far more appropriate and dignified system that does not impede on the socio-cultural background. Key words: Porta Potty sanitation system, informal settlements, socio-cultural perceptions, users and Jim Se Bos.
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in fulfilment of the requirements for the degree of Masters of Built Environment in Housing Johannesburg 2014
Keywords: Squatter settlements--South Africa--Cape Town; Water resources development|zAfrica, Southern; Water resources development|zAfrica, Southern; City planning--South Africa--Cape Town.